Isrun Engelhardt (1941-2022). In Memoriam - González, Jorge M. (Anartia, 2022)
It was around 2009 when I met Isrun. I was researching about Ernst Schäfer’s times in Venezuela, when I was suggested to contact her. Isrun (Fig. 1) was a worldwide recognized Tibetan historian, who had thoroughly researched the 1938-1939 Schäfer-Tibet expedition probing that contrary to myth and misinterpretations, it was truly a scientific endeavor, “in intention and execution” (Anonymous 2022). I discussed with her all the information I had already gathered from my investigation sources and she, without hesitation, shared articles and information she had obtained on the bright and complex explorer and naturalist.